Analisis Faktor yang Berpengaruh dalam Swamedikasi Antibiotik pada Ibu Rumah Tangga di Kelurahan Kajen Kebupaten Pekalongan - Ady Restiyono (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2016)
ABSTRACTSwamedication had been known in society especially housewives for treating some mild disseases. Antibiotic is one of the drugs which is often used irrationally by housewives. This research aims to analyze factors influence in antibiotic swamedication by hosewives at Kelurahan Kajen Kabupaten Pekalongan. This research was done analitically with cross sectional approach. By using proportional random sampling technique, 300 hosewives as sample has been investigated and showes that more house wives are not doing antibiotics swamedication (59%) than do. The most influential factors in antibiotics swamedication by housewives are knowladge about antibiotic (OR=5.307, p=0,000) so, good knowladge likely 5.307 times not doing antibiotic swamedication, and source of information of antibiotics (OR=29,94, p=0.0005) so, good source of information of antibiotics likely 29.94 times not doing antibiotic swamedication.Keywords: swamedication, antibiotic, housewife